2022
DOI: 10.3892/etm.2022.11191
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Sestrin2 overexpression in diabetic cardiomyopathy ameliorates cardiac injury via restoration of mitochondrial function

Abstract: Mitochondrial dysfunction-induced apoptosis plays a crucial role in the progression of diabetic cardiomyopathy (DCM). Sestrin2 is an important oxidative stress response protein and is involved in the maintenance of mitochondrial function, especially under stress. The aim of the present study was to investigate the role of Sestrin2 in DCM and to explore the underlying mechanisms. H9c2 cardiomyocytes were induced with high glucose (HG) medium (33 mmol/l glucose) for an in vitro DCM model. C57BL/6 mice were induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Sestrin2, a conserved antioxidant and metabolic regulator, markedly reprogram intracellular signaling pathways [25]. Currently, Sestrin2 was extensively explored in multi-diseases, such as diabetic cardiomyopathy, cholestatic liver injury, idiopathic pulmonary fibrosis, cancers [5,[26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Sestrin2, a conserved antioxidant and metabolic regulator, markedly reprogram intracellular signaling pathways [25]. Currently, Sestrin2 was extensively explored in multi-diseases, such as diabetic cardiomyopathy, cholestatic liver injury, idiopathic pulmonary fibrosis, cancers [5,[26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…reported that Sestrin2 may enhance antioxidative actions and alleviate mitochondrial lesion by interacting with Nrf2 to prevent the diabetic rat heart from ischemia/reperfusion injury ( 18 ). Our previous research showed that inhibition of enhanced Sestrin2 expression attenuates cardiac injury in DCM, which may be mainly attributed to the restoration of mitochondrial function ( 127 ). Some antiglycemic agents, such as metformin and empagliflozin, were found to be cardioprotective through Sestrin2-associated mechanism.…”
Section: The Roles Of Sestrin2 In Diabetic Complicationsmentioning
confidence: 99%
“…However, other academics have a different viewpoint. Zhang et al [56] recently set out to investigate the role of SESTRIN2 in diabetic cardiomyopathy using H9C2 cardiomyocytes and DCM-induced C57BL/6 mice. Their findings suggest that inhibiting SESTRIN2 expression improves cardiac dysfunction in DCM, possibly due to the restoration of mitochondrial dysfunction-induced apoptosis.…”
Section: Diabetic Cardiomyopathymentioning
confidence: 99%